Poetics of great absurdity and the pedal rhythm of Trilce - Coello, Óscar (2014)
This article shows some notes about the poetic adventure of Trilce, from the general level of the conception of the artwork to the specific level of the verse production, where the rhythm of pedal cadence acts as axis that structures the senses with the lost syntax of speech.